2012
DOI: 10.1016/s0140-6736(12)60195-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary cardiosphere-derived cells for heart regeneration after myocardial infarction (CADUCEUS): a prospective, randomised phase 1 trial

Abstract: Summary Background Cardiosphere-derived cells (CDCs) reduce scarring after myocardial infarction, increase viable myocardium, and boost cardiac function in preclinical models. We aimed to assess safety of such an approach in patients with left ventricular dysfunction after myocardial infarction. Methods In the prospective, randomised CArdiosphere-Derived aUtologous stem CElls to reverse ventricUlar dySfunction (CADUCEUS) trial, we enrolled patients 2–4 weeks after myocardial infarction (with left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
998
1
18

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,285 publications
(1,029 citation statements)
references
References 32 publications
12
998
1
18
Order By: Relevance
“…These cells highly expressed CXCR4 under hypoxic preconditioning (HPC), and were able to migrate to injured myocardium after intravenous injection (Tang et al, 2009). A phase 1 clinical trial of CDCs treatment has been recently carried out in patients 2-4 weeks after acute myocardial infarction (Makkar et al, 2012). Treatment with CDCs was reported to significantly reduce infarct size and increase viable heart mass at 6 months, but without significant improvement in LVEF.…”
Section: Cardiosphere-derived Cellsmentioning
confidence: 99%
“…These cells highly expressed CXCR4 under hypoxic preconditioning (HPC), and were able to migrate to injured myocardium after intravenous injection (Tang et al, 2009). A phase 1 clinical trial of CDCs treatment has been recently carried out in patients 2-4 weeks after acute myocardial infarction (Makkar et al, 2012). Treatment with CDCs was reported to significantly reduce infarct size and increase viable heart mass at 6 months, but without significant improvement in LVEF.…”
Section: Cardiosphere-derived Cellsmentioning
confidence: 99%
“…Mesenchymal stem cells are currently under clinical investigation as a treatment to improve myocardial function and perfusion in patients with advanced heart failure after myocardial infarction 2, 3. The main benefit of mesenchymal stem cells may be derived from the bioactive encapsulated molecules they secrete in the form of EVs 7.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 1 clinical trials demonstrate that intracoronary infusion of cardiosphere‐derived cells is efficacious in patients with advanced heart failure after myocardial infarction 2, 3. However, larger‐cohort studies have failed to show a lasting clinical benefit 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…43,53,54,62 Heart Failure Additionally, there have been multiple HF trials (Table 2). Many demonstrated benefits in ventricular function noted by increased EF, [68][69][70][71][72][73]75,79,82,83 improved functional class, 75,78,80,82,83,86 reduced infarct size, 70,72,80,[82][83][84] decreased mortality, 79 and acceptable safety outcomes. [66][67][68][69]75,78,80,[82][83][84]86 SCIPIO was the first trial using autologous CSC in HF and showed improvement in EF, infarct size, viable tissue, and HF scores.…”
Section: Clinical Outcomes Acute Myocardial Infarctionmentioning
confidence: 99%
“…79 Some trials did not show significant results, 76,85 while others demonstrated benefits, but no effect on EF. 66,67,74,77,80,84,86 A highly anticipated trial, FOCUS-CCTRN, assessed BMC via transendocardial injection in chronic HF. However, results indicated no significant change in endpoints.…”
Section: Clinical Outcomes Acute Myocardial Infarctionmentioning
confidence: 99%